TRANSCHOROIDAL SUBRETINAL CHIP IMPLANTATION IN BLIND RETINAL PIGMENTOSA PATIENTS. THE CHOROIDAL CHALLENGE - G. Sachs Helmut (Российский офтальмологический журнал)
Purpose: Active subretinal visual prostheses require a transchoroidal implantation due to their necessary connection to extraocular parts of the device for energy supply. When starting the program surgically the choroidal access was assumed to be one of the major problems. Material and Methods: 26 legally blind retinal pigmentosa (RP) patients were included in the multicenter study and implanted with a chronic active prosthetic device via a transchoroidal access. 12 out of these 26 patients were operated by one surgeon who developed the transchoroidal procedure and had experience with it. Only this subgroup was analyzed to eliminate the learning curve effects of multiple surgeons. Results: All implantations were carried out successfully in terms of intended position of the implant and stability of the retinal situation. Feared major bleedings were not observed even when accidental perforation of the choroid occurred (1) in the area of the posterior pole. Minor problems concerning surgery were observed when advancing the guide foil or the implant subretinally. The reason were adhesions between retinal pigment epithelium (RPE) and retina. These adhesions seem common in the area of dense pigmentation or scaring in RP patients. Other technical problems during the complex surgical procedure were unintended sub RPE implantation. This occurred twice but could be corrected within the implantation. This pitfall never led to bleedings or other unexpected effects that were harmful for the patient. Conclusion: Problems resulting from the choroid are manageable and seem not to be a limiting factor for this complex surgical procedure. Unintended perforations that occurred did not have a threatening or harmful decisive side effect. One of the reasons may be the rather atrophic choroidal situation in RP. Proper design and geometry of the guide foil and implant are relevant and are under improvement to minimize incidents resulting from this challenge. Thus even difficult retinal situations are no contraindication for chip implantation // Russian Ophthalmological Journal, 2016; 2: 27-32. doi: 10.21516/2072-0076-2016-9-2-27-32 .